2017
DOI: 10.1021/acs.chemmater.6b04597
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Process for Direct Atomic Layer Deposition of Metallic Cu Thin Films Based on an Organic Reductant

Abstract: We report a promising approach to use an organic reductant for in situ atomic layer deposition (ALD) of metallic copper films. The process is based on sequentially pulsed precursors copper acetyl acetonate (acac), water, and hydroquinone (HQ) and yields crystalline copper films at temperatures as low as <200 °C with an appreciably high deposition rate of ∼2 Å/cycle. Deposition parameters are explored for the process m × [n × (Cu(acac) 2 −H 2 O)−HQ] with several values of m and n, keeping m × n fixed to 500. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
0
26
0
1
Order By: Relevance
“…The films were highly crystalline and therefore the surface roughness was too high for the XRR data to be used for film thickness determination; however, the XRR data were used to estimate the film densities from the critical angles. The film thicknesses were estimated with AFM (TopoMetrix Explorer) using the cantilever tip jump technique; the as‐deposited films were stable even when left in ambient conditions for several days. The surface topography and RMS roughness measurements were performed using the same AFM in the contact mode.…”
Section: Methodsmentioning
confidence: 99%
“…The films were highly crystalline and therefore the surface roughness was too high for the XRR data to be used for film thickness determination; however, the XRR data were used to estimate the film densities from the critical angles. The film thicknesses were estimated with AFM (TopoMetrix Explorer) using the cantilever tip jump technique; the as‐deposited films were stable even when left in ambient conditions for several days. The surface topography and RMS roughness measurements were performed using the same AFM in the contact mode.…”
Section: Methodsmentioning
confidence: 99%
“…Then, comparing the Cu(dmap)2+HQ process developed here with the similar process where Cu(acac)2 was used as the copper precursor, it was found that while the Cu(acac)2+HQ process yielded metallic Cu films thorough a wide deposition temperature range, 51 the Cu(dmap)2+HQ process is temperature dependent such that it results in metallic Cu films only at the higher deposition temperatures; at temperatures below 120 o C the process successfully yielded hybrid Cu-HQ films. Also importantly, the as-deposited amorphous hybrid films were strongly air and moisture sensitive and crystallised upon the reaction with water.…”
Section: Discussionmentioning
confidence: 94%
“…In the case of HQ as the organic precursor, it was interesting to observe the effect of the deposition temperature: at the higher deposition temperatures the Cu(dmap)2+HQ process yielded metallic Cu films like in our previous study with Cu(acac)2 as the copper precursor. 51 However, the low sublimation temperature of Cu(dmap)2 allowed us to carry out depositions also in the lower temperature range of 100-120°C where amorphous Cu-organic films were obtained. With ODA, amorphous hybrid films were obtained at deposition temperatures up to ~220 °C, whereas at 240 °C the Cu(dmap)2+ODA process too yielded metallic Cu films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It was observed that the basics of nickel thin-film deposition using plasma-enhanced ALD are transferable from the sapphire substrate to aluminum oxide foams. In addition to this particular application, the ability to deposit pure metallic thin films has several applications in metallization, 43,44 solar cell cathodes, 45 and solid oxide fuel cells, 46 among others.…”
Section: Resultsmentioning
confidence: 99%